2019
DOI: 10.1016/j.jdent.2019.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of 8% arginine on dentin hypersensitivity: A multicenter clinical trial in 273 patients over 24 weeks

Abstract: OBJECTIVES To assess the efficacy of 8% arginine containing prophylaxis products over 24 weeks in subjects with dentin hypersensitivity (DH). METHODS 297 patients with established DH (Schiff score 2, 3) in three European study centers were randomly assigned to either 8% arginine and calcium carbonate in-office prophylaxis paste and the respective toothpaste (test group) or fluoride-free prophylaxis paste and sodium monoflourophosphate toothpaste as a negative control group. Air blast (Schiff Score) and tactile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 27 publications
1
5
0
2
Order By: Relevance
“…However, the model pattern for the samples treated with saliva immersion suggests that the effectiveness of proargin would require a longer period than seven days to effectively occlude the tubules. This is in agreement with the recent clinical finding that proargin achieved significant relief of DH after application for 24 weeks [3].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…However, the model pattern for the samples treated with saliva immersion suggests that the effectiveness of proargin would require a longer period than seven days to effectively occlude the tubules. This is in agreement with the recent clinical finding that proargin achieved significant relief of DH after application for 24 weeks [3].…”
Section: Discussionsupporting
confidence: 93%
“…A previous study [2] reported that more than 80% of children and up to 43% of adult's population suffer from dental pain associated with DH. More worrisome is that DH negatively affects the quality of life of dental patients if left untreated [3]. Consequently, numerous dentin remineralization strategies have been proposed in the literature [4, 5] for the management of DH.…”
Section: Introductionmentioning
confidence: 99%
“…It may also be attributed to the placebo effect which was common in the clinical studies of desensitizing pastes. Placebo products could reduce hypersensitivity by as much as 40% from baseline and therefore have an effect on the efficacy measurement of test dentifrice [31]. Another factor may be the Hawthorne effect.…”
Section: Discussionmentioning
confidence: 99%
“…44 This notwithstanding, Colgate brands like calcium–arginine combination have been reported to be highly effective in occluding dentin tubules. 45,46…”
Section: Discussionmentioning
confidence: 99%